1961
DOI: 10.1079/bjn19610066
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the voluntary intake of food by cows

Abstract: It has often been supposed that the amount of roughage cows will voluntarily consume at any one meal is largely determined by the effect of that meal in filling the reticulo-rumen and giving rise to a feeling of satiety (cf. Kruger & Miiller, 1955; Makela, 1956). Earlier experiments (Campling & Balch, 1961) provided direct evidence of a relationship between the amount of the contents of the reticulo-rumen and the voluntary intake of hay. There have, however, been few measurements of the amount of digesta in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1970
1970
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(36 citation statements)
references
References 11 publications
5
31
0
Order By: Relevance
“…The straw used in the diets in the present experiment was chopped rather than ground in an attempt to avoid the various complications associated with the use of ground roughages; these complications include increased intake and rate of passage, decreased digestibility, absence of true rumination and a possible limiting effect of hind gut capacity on intake (Campling & Freer, 1966). It is difficult to estimate the VOl.…”
Section: I970mentioning
confidence: 99%
See 3 more Smart Citations
“…The straw used in the diets in the present experiment was chopped rather than ground in an attempt to avoid the various complications associated with the use of ground roughages; these complications include increased intake and rate of passage, decreased digestibility, absence of true rumination and a possible limiting effect of hind gut capacity on intake (Campling & Freer, 1966). It is difficult to estimate the VOl.…”
Section: I970mentioning
confidence: 99%
“…The net amount of digestion occurring in the reticulo-rumen was estimated by means of the ligninratio technique (Balch, 1957;Campling, Freer & Balch, 1961); samples of digesta were taken from a point close to the reticulo-omasal orifice, five times daily over a period of 5 d, and were bulked for analysis.…”
Section: Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Then the latter concluded that the maximal appetite of animals for feed is determined to a considerable extent by the feed residues present in their digestive tracts. CAMPLING et al 25) showed that the differences in the voluntary intake of hay and straw in cows were explicable on the basis of the differences in the retention time of feed residues in their digestive tract, or the amounts of digesta in the rumen.…”
Section: Discussionmentioning
confidence: 99%